KEEFEKTIFAN MODEL PROBLEM BASED LEARNING DENGAN MEDIA ULAR TAPA DALAM MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA KELAS V SDN JEMBANGAN 01 - Khusna, Isnaini; Wawan Shokib Rondli; Ika Ari Pratiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to measure the effectiveness of using the Problem-Based Learning model with the Ular Tapa media in the Pancasila Education subject for fifth-grade students at SDN Jembangan 01. This quantitative research was conducted using an experimental method with a one-group pretest-posttest design. The study was carried out during the even semester of the 2024/2025 academic year. All 28 fifth-grade students at SDN Jembangan 01 were selected as the sample for this research. This study employed a paired sample t-test to determine the significance of the improvement in learning outcomes between the pretest and posttest. The results of the paired sample t-test analysis showed a significance value of -37.371. The results of the N-Gain test calculation showed an N-Gain score of 0.7379, which is classified as high. Meanwhile, the N-Gain percentage was found to be an average of 73.7821, indicating a fairly effective level